Duality and o − O-structure in non reflexive Banach spaces - Luigi D'Onofrio; Carlo Sbordone; Roberta Schiattarella (Atti della Accademia Peloritana dei Pericolanti : Classe di Scienze Fisiche, Matematiche e Naturali, 2020)

(untitled)
Let E be a Banach space with a supremum type norm induced by a collection of functionals ℒ ⊂ X* where X is a reflexive Banach space. Familiar spaces of this type are BMO, BV, ...